Comparison of the Effectiveness of the Integrative Cognitive–Emotional Couple Reconstruction Package for Infertile Women and Unified Transdiagnostic Couple Therapy on Marital Intimacy and Empathy - Ahmadi, Sanaz; Golparvar, Mohsen; Yousefi , Zahra (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study aimed to compare the effectiveness of a combined cognitive–emotional reconstruction (CER) therapy package and integrative transdiagnostic couple therapy in improving emotion regulation and affective capital among infertile women.Methods and Materials: The research employed a quasi-experimental design with three groups—CER therapy, integrative transdiagnostic couple therapy, and a control group—using a pretest–posttest design with a two-month follow-up. The statistical population included infertile women attending infertility centers in Isfahan during the winter of 2025. A total of 54 participants were selected via purposive sampling and randomly assigned to three groups of 18. The CER group received ten 60-minute sessions of cognitive–emotional reconstruction therapy, while the transdiagnostic group underwent ten 60-minute sessions of integrative couple therapy. The Gross and John (2003) Emotion Regulation Questionnaire and the Golparvar (2018) Affective Capital Questionnaire were administered at pretest, posttest, and follow-up. Data were analyzed using repeated-measures ANOVA and Bonferroni post hoc tests in SPSS 26.Findings: Both interventions significantly improved emotion regulation (reappraisal and suppression) and affective capital compared to the control group (p < .01). The CER therapy produced a greater increase in cognitive reappraisal and affective capital, whereas both interventions were equally effective in reducing emotional suppression. The effect sizes were large across outcomes (η² = .69–.83), and all treatment effects remained stable at the two-month follow-up, indicating the durability of therapeutic gains.Conclusion: The results confirm that both CER therapy and integrative transdiagnostic couple therapy effectively enhance emotion regulation and affective capital in infertile women. The CER approach showed superior outcomes in promoting positive emotional resources, suggesting its particular utility for strengthening psychological resilience and marital well-being in infertility counseling settings.